Development and Evaluation of an Infusion of Red Tea (Camellia sinensis) with Blackberry (Rubus ulmifolius) Enriched with beta-Glucans for the Control Glycemia in Diabetic Persons - Di Iorio, Adriana Beatriz; Castillo, Crista; Naranjo, Luis David; Espinal, Raúl; Molina, Donald Francisco; Boully, Ludovic; Arévalo, Ana Carolina; Chinchilla, Jose Miguel; Deyse Gurak, Poliana (Acta Scientific Publications OPC Private Limited, 2020)
Introduction: An infusion of red tea with blackberries enriched with ¿-glucans for glycemic control in diabetic subjects was developed and evaluated by virtue of a high percentage of people using plant extracts as traditional medicine to meet their primary health care needs. Materials and Methods: A completely randomized block design was used to evaluate concentrations of red tea with dehydrated blackberry (50/50 and 75/25), temperatures (75 and 95°C) and infusion times (2 and 5 minutes) for preparation of beverage with higher content of total polyphenols. The selected treatment was evaluated in 30 diabetics for 28 days, who underwent anthropometric measures (weight, height, waist-hip circumference and blood pressure), biometric (glucose and cholesterol) and performed and food intake was analyzed through a 24-hour reminder. Results: The treatment with higher content of polyphenols was obtained with 75/25 red tea with blackberry, 95ºC and infusion for 5 minutes. Tea intake was associated with reductions in anthropometric measures of Body Mass Index (BMI) and Waist-to-Hip Index (WHI). Conclusion: It was possible to extract greater content of total polyphenols with longer infusion temperature and time. There was a greater reduction in BMI at ages 45 - 65 years, glucose levels at ages 45 - 65 and > 65 years, total cholesterol levels at ages 45 - 65 years and diabetic patients had a normal distribution of dietary intake macronutrients